Nonlinear optical functionalities of VO2- and GaN-based nanocomposites - Mundry, Jan (Technische Universität Dortmund, 2022)
This thesis presents fundamental research and concepts for active photonic elements operating in the telecom wavelength regime. The aim of the study is to determine the characteristics of the investigated nanostructures and to evaluate the implementation of the proposed materials in potential optical devices. In the first part of this thesis the optical properties as well as the photonic application of vanadium dioxide (VO2) nanocrystals (NCs) are studied. VO2 exhibits an easily accessible insulator-to-metal phase transition (IMT) near ambient temperatures. Upon excitation it undergoes an atomic rearrangement that is accompanied by a substantial modification of the complex dielectric function. When VO2 undergoes the IMT, the near-infrared transmission peaks of a moderate-finesse etalon containing a sub-wavelength layer of VO2 NCs are found to markedly shift in their spectral position and peak transmissivity. Both heat deposition and optical excitation permit to actively control the etalon’s functionality. Much less is known about the nonlinear optical properties of VO2 beyond the established IMT. To this end the nonlinear optical response of a thin film of VO2 NCs is investigated with open aperture z-scans involving femtosecond near-infrared pulses. A pronounced saturable absorption on the short-wave side of the resonance as well as a marked reverse saturable absorption in the telecom window are observed. The results hold promise for the use of VO2 nanocrystals as a saturable absorber, e.g., to mode-locked near-infrared lasers. In the second part a semiconductor heterostructure based on hexagonal ultranarrow GaN/AlN multi-quantum wells (MQWs) is investigated. The tailored inter-miniband (IMB) transition is characterized in terms of its linear as well as ultrafast nonlinear optical properties using the established pump-probe scheme. In line with theoretical predictions for LO-phonon scattering, a fast relaxation is found for resonant IMB excitation. In stark contrast, significantly larger relaxation times are observed for photon energies addressing the above barrier continuum. The last section reports on a new type of nonlinear metasurface taking advantage of these telecom-range IMB transitions. The heterostructure is functionalized with an array of plasmonic antennas featuring cross-polarized resonances at these near-infrared wavelengths and their second harmonic. This kind of nonlinear metasurface allows for substantial second harmonic generation at normal incidence which is completely absent for an antenna array without the heterostructure underneath.
Keywords: Photonics; Nonlinear optics; Spectroscopy; Z-scan; Saturable absorption; Plasmonics; Nanocrystal; Vanadium dioxide; Semiconductor; Gallium nitride; Superlattice; Multi quantum well; Second harmonic generation; 530; Photonik; Nichtlineare Optik; Spektroskopie; Sättigbare Absorption; Plasmonik; Nanokristall; Vanadiumdioxid; Halbleiter; Galliumnitrid; Übergitter; Quantenwell; Frequenzverdopplung